Histomorphology of germ cell tumors at various anatomic sites: a 5 years study at a tertiary care centre - Lateef, Manal A.; Lone, M. I. (International Journal of Research in Medical Sciences, 2021)
Background: Germ cell tumors (GCTs) are a heterogeneous group of neoplasms, which occur in the gonads, and at extra gonadal sites of the body. The aim of the study was to observe the different histopathological patterns of various GCTs in the body at all possible sites and to know their IHC staining patterns. Methods: The study was conducted for a period of 5 years from 2015 to 2019 and was an observational study. The recorded data was compiled and entered in a spreadsheet and then exported to data editor of SPSS Version 20.0. Continuous variables were expressed as mean SD and categorical variables were summarized as frequencies and percentages. Graphically the data was presented by bar and pie diagrams Chi-square test or Fisher’s exact test was applied for comparing categorical values. P<0.05 was considered statistically significant. All p values were 2 tailed. Results: A total of 93 cases were analyzed and the mean age of the patients was 27.8 years. Mature cystic teratoma was the most common histopathological variant and was mostly seen in the ovaries. There was a difference in age predilection of benign and malignant tumors. Most of the malignant GCTs were gonadal while EGCTs were likely to be benign. MGCTs (mixed GCTs) were mostly testicular in origin with only one MGCT being extragonadal. Conclusions: Mature cystic teratomas were the most frequent GCTs with frequent site being in ovaries. Out 0f 18 EGCTs only 2 were malignant, rest all were mature cystic teratomas.